2020
DOI: 10.1016/j.oneear.2020.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Reaching New Heights in Plastic Pollution—Preliminary Findings of Microplastics on Mount Everest

Abstract: Highlights d Microplastics were found in snow and stream water samples on Mt. Everest d The highest microplastics were discovered in a sample from 8,440 m.a.s.l. d Most microplastics were polyester fibers, likely from clothing and equipment d Technological advances could minimize microplastic pollution from exploration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
160
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 402 publications
(206 citation statements)
references
References 42 publications
(61 reference statements)
4
160
2
1
Order By: Relevance
“…Outdoor microfibers can be carried by the wind and can fall as dust in the city [ 110 ] or in remote areas, as reported for lakes in Mongolia [ 111 ] and the Pyrenees [ 95 ]. A recent study reported the presence of polyester microfibers on Mount Everest, probably from clothing and equipment based on the detection of greater concentrations of microfibers near major camping sites [ 112 ]. Furthermore, precipitation can trap airborne microfibers and deposit them on the ground [ 95 , 113 ].…”
Section: Use Phasementioning
confidence: 99%
“…Outdoor microfibers can be carried by the wind and can fall as dust in the city [ 110 ] or in remote areas, as reported for lakes in Mongolia [ 111 ] and the Pyrenees [ 95 ]. A recent study reported the presence of polyester microfibers on Mount Everest, probably from clothing and equipment based on the detection of greater concentrations of microfibers near major camping sites [ 112 ]. Furthermore, precipitation can trap airborne microfibers and deposit them on the ground [ 95 , 113 ].…”
Section: Use Phasementioning
confidence: 99%
“…That scarp cuts into an earlier massive rockslide--the Khumjung slide, which is currently the sixth-largest rockslide documented in Nepal [ 12 ]. This massive rockslide resulted from a 2.1 × 109 m 3 volume of rock material sliding southward off the Khumbila peak, where remnants make up the small E–W-trending ridge that separates Khumjung and Kunde from Namche [ 4 ]. Rockslides of this magnitude are thought to account for a large percentage of the erosion across the high-relief Himalaya [ 13 , 14 ].…”
Section: Physical Environmentmentioning
confidence: 99%
“…Everest was considered the highest junkyard in the world [ 83 ]. More recently, the field team from this expedition found many items such as plastic bottles, oxygen bottles, food wrappers, food waste, and cigarette butts [ 4 ].…”
Section: Chemical Risksmentioning
confidence: 99%
See 2 more Smart Citations